Sustainability Management and Business Strategy in Asia - Kokubu, Katsuhiko [Ed.]; Nagasaka, Yoshiyuki [Ed.] (London : World Scientific, 2020)
"Sustainability is a concept that unifies the environment, economy, and society, and has spread as a key concept in enterprise management. The United Nations adopted the Sustainable Development Goals (SDGs) in 2015, which require worldwide efforts to reach a sustainable society, and also applies to private enterprises. Sustainability should be developed in connection with management strategy, and Asia's role, including that of Japan, is important to improve global sustainability. This book addresses how sustainability management in the Asian context is currently practised and proposes practices for the future. Investigation of the effect of business domain characteristics on the integration of sustainability and management, and elucidation of the process and features of EMCS (Environmental Management Control System) inside and outside of companies have been indicated. The book points that companies need to use and design Sustainability Management Control Systems in order to implement a CSR (Corporate Social Responsibility) strategy and match employees' behavior to CSR activities"--
Keywords: Management -- Environmental Aspects; Sustainable Development